Auditoría de las bases de datos de gestión académica de las instituciones de educación superior públicas de Manabí - Frank Montesdeoca, Juan José (2016)
The importance of the audit database is the need to mitigate risks in data loss, such eventualities are strong threat to an institution, since the data contained in the information systems are exposed to any eventuality; the audit applied to public institutions of higher education of Manabi, allowed assessing data protection, safety and effectiveness of its processes, all this was done using a methodical and timely examination allowed to know their status, bringing out irregularities It is presenting their inappropriate administration. As a guide to audit the OCTAVE methodology was used, the same that allowed a national and international analysis and subsequent assessment of the risks that fall on their databases, in the same way a study of norms and standards in force was made, , which gave the pattern for how should be safety, quality, management and protection of their data, for verification of these results the coefficient matching Kendall, which measure the degree correlation was used for each of the applied questions, which resulted in a concordance 0.13, concluding that the audited entities have a low compliance INEN ISO / IEC 27000 standard.